1988
DOI: 10.1007/bf00247498
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic neurons containing somatostatin-like immunoreactivity in the rat hippocampus and dentate gyrus

Abstract: The distribution of somatostatin-like immunoreactive (SS-LI) material and its colocalization with glutamic acid decarboxylase (GAD)-like immunoreactivity were studied in the rat hippocampus and dentate gyrus neurons using immunohistochemistry. In the dentate gyrus and CA1 region, SS-LI perikarya were concentrated in the hilus and in the stratum oriens, respectively, whereas immunoreactive cell bodies were rarely seen in other layers. Approximately half of the SS-LI neurons of the CA3 region were situated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
120
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(133 citation statements)
references
References 23 publications
13
120
0
Order By: Relevance
“…2b, arrow) also coincide with those of O-LM cells. Numerous studies have shown that all O-LM cells express the neuropeptide SOM and that SOM expression in the hippocampus defines a subset of GABAergic interneurons (Köhler and ChanPalay, 1982;Morrison et al, 1982;Johansson et al, 1984;Sloviter and Nilaver, 1987;Kosaka et al, 1988;Kunkel and Schwartzkroin, 1988;Milner and Bacon, 1989;Esclapez and Houser, 1995). As illustrated in Figure 3d-l, fluorescence immunohistochemistry showed a striking overlap between EGFP-and SOM-expressing interneurons of the hippocampus.…”
Section: Hippocampal Egfp-expressing Cells Are Somatostatinexpressingmentioning
confidence: 76%
“…2b, arrow) also coincide with those of O-LM cells. Numerous studies have shown that all O-LM cells express the neuropeptide SOM and that SOM expression in the hippocampus defines a subset of GABAergic interneurons (Köhler and ChanPalay, 1982;Morrison et al, 1982;Johansson et al, 1984;Sloviter and Nilaver, 1987;Kosaka et al, 1988;Kunkel and Schwartzkroin, 1988;Milner and Bacon, 1989;Esclapez and Houser, 1995). As illustrated in Figure 3d-l, fluorescence immunohistochemistry showed a striking overlap between EGFP-and SOM-expressing interneurons of the hippocampus.…”
Section: Hippocampal Egfp-expressing Cells Are Somatostatinexpressingmentioning
confidence: 76%
“…In the hippocampus, somatostatin is produced in a variety of inhibitory neurons including hilar interneurons, bistratified cells, and O-LM interneurons in the Ammon´s horn [24]. Somatostatin cells in the hilus make up to 16% of total inhibitory interneurons in the dentate gyrus [31]. The terminals of these cells are in the outer molecular layer and presumably affect perforant path excitatory synapses [32].…”
Section: Somatostatinmentioning
confidence: 99%
“…CST, that interacts with SST receptors, is not robustly expressed in hilus in young adult rodents (de Lecea et al, 1996), however in immature and aged rodents its expression is more robust (de Lecea et al, 1997;Winsky-Sommerer et al, 2004). SST interneurons represent about 16% of the total GAD-expressing (GABAergic) neurons in the dentate region (Kosaka et al, 1988), and have axons that terminate on the distal dendrites of granule cells in the outer molecular layer, accounting for the thick plexus of SST immunoreactivity in this region in humans and rats (Amaral et al, 1988;Austin and Buckmaster, 2004;Csaba et al, 2005;Leranth et al, 1990;Milner and Bacon, 1989). Interestingly, SST terminals on granule cell dendrites are often closely apposed by SSTnegative asymmetric (excitatory terminals), presumably perforant path synapes (Leranth et al, 1990;Milner and Bacon, 1989).…”
Section: Seizures Induce the Loss Of Sst-containing Interneurons In Tmentioning
confidence: 99%